n-type CdTe:In for photovoltaics: in situ doping, type verification and compensation effects - Theodore D C Hobson; Luke Thomas; Laurie J Phillips; Leanne A H Jones; Matthew J Smiles; Christopher H Don; Pardeep K Thakur; Huw Shiel; Stephen Campbell; Vincent Barrioz; Vin Dhanak; Tim Veal; et al. (JPhys Energy, 2023)
We explored the in-situ doping of cadmium telluride thin films with indium to produce n-type absorbers as an alternative to the near-universal choice of p-type for photovoltaic devices. The films were grown by close space sublimation from melt-synthesised feedstock. Transfer of the indium during film growth was limited to 0.0014%–0.014%—unless reducing conditions were used which yielded 14%–28% efficient transport. While chunks of bulk feedstock were verified as n-type by the hot probe method, carrier type of thin film material was only able to be verified by using hard x-ray photoelectron spectroscopy to determine the Fermi level position within the band gap. The assignment of n-type conductivity was consistent with the rectification behaviour of a p-InP/CdTe:In junction. However, chloride treatment had the effect of compensating n-CdTe:In to near-intrinsic levels. Without chloride, the highest dopant activation was 20% of the chemical concentration of indium, this being for a film having a carrier concentration of n = 2 × 10 ^15 cm ^−3 . However, the activation was often much lower, and compensation due to over-doping with indium and native defects (stoichiometry) are discussed. Results from preliminary bifacial devices comprising Au/P3HT/ZnTe/CdTe:In/CdS/FTO/glass are presented.